Radioguided Surgery for Meckel Diverticulum: Nuclear Medicine Aspects. (March 2020) - Medaer, Eva; Miserez, Marc; De Hertogh, Gert; Van Laere, Koen; Deroose, Christophe M.
Abstract : Abstract: We present the case of a 13-year-old boy with bleeding complications from a Meckel diverticulum (MD), which was scintigraphically confirmed. A first exploratory laparoscopy was unsuccessful in identifying the diverticulum. A new 99m Tc-pertechnetate scintigraphy (including SPECT/CT), 3 years later, suggested the anatomical location and was helpful during the surgical exploration for the MD by radioguided surgery. Radioguidance is helpful in pathologies characterized by small size or variable anatomical location. A MD with ectopic gastric mucosa can be distinguished from the rest of the small bowel based on selective 99m Tc-pertechnetate uptake in the gastric mucosa, with limited background activity.